Freud and the Post-Freudians - "Brown, J.A.C." ("Middlesex, Eng.", 1983)
This work provides a compelling account of both Freud's original ideas and of the subsequent developments that arose out of them, explaining the basic concepts of psychoanalytic theory, including a survey of the contribution of Freud's contemporaries.
Keywords: Psychology